2003
DOI: 10.1021/ic025849q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroelectrochemical Studies of Mixed Heteroleptic Chelate Complexes of Ruthenium(II) with 1,8-Bis(2-pyridyl)-3,6-dithiaoctane (pdto) and Substituted 1,10-Phenanthrolines

Abstract: Reaction of dichlorotris(triphenylphosphine) ruthenium(II) [RuCl(2)(PPh(3))(3)] with 1,8-bis(2-pyridyl)-3,6-dithiaoctane (pdto), a (N(2)S(2)) tetradentate donor, yields a new compound [Ru(pdto)(PPh(3))Cl]Cl (1), which has been fully characterized. (1)H and (31)P NMR studies of 1 in acetonitrile at several temperatures show the substitution of both coordinated chloride and triphenylphosphine with two molecules of acetonitrile, as confirmed by the isolation of the complex [Ru(pdto)(CH(3)CN)(2)]Cl(2) (2). Cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
0
32
0
2
Order By: Relevance
“…For synthesis of the complexes, solvents were degassed with Ar for 30 min before use. [{RuCl 2 (PPh 3 ) 3 } 2 ] was synthesized following a standard procedure [18].…”
Section: Methodsmentioning
confidence: 99%
“…For synthesis of the complexes, solvents were degassed with Ar for 30 min before use. [{RuCl 2 (PPh 3 ) 3 } 2 ] was synthesized following a standard procedure [18].…”
Section: Methodsmentioning
confidence: 99%
“…Following literature methods [24,25], which report the synthesis of [RuCl 2 (PPh 3 ) 3 ] from commercial RuCl 3 ⋅ 3H 2 O, we prepared [RuCl 2 (PPh 3 ) 3 ] from elemental Ruthenium without isolating the intermediate Ru(III)-chloride: A mixture of Ruthenium powder (0.750 g, 7.42 mmol), NaOH (4.00 g, 100 mmol) and NaClO 3 (2.63 g, 24.7 mmol) was cautiously heated in a crucible (using a Bunsen burner) for 15 min (until the evolution of gas from the deep red melt ceased). The mixture was allowed to cool to ambient temperature and was then dissolved in conc.…”
Section: Synthesis Of [Rucl 2 (Pph 3 ) 3 ]mentioning
confidence: 99%
“…Following literature methods [24,25] mmol), NaOH (4.00 g, 100 mmol) and NaClO 3 (2.63 g, 24.7 mmol) was cautiously heated in a crucible (using a Bunsen burner) for 15 min (until the evolution of gas from the deep red melt ceased). The mixture was allowed to cool to ambient temperature and was then dissolved in conc.…”
Section: Synthesis Of [Rucl 2 (Pph 3 ) 3 ]mentioning
confidence: 99%
“…Ru(PPh 3 ) 3 Cl 2 and Ru(Phen)(DMSO) 2 Cl 2 were prepared via literature methods. [11][12][13] Acetonitrile used for electrochemical analysis was distilled off P 4 O 10 under N 2 . UV-Vis spectra were obtained using a Perkin-Elmer Lambda-35 UV-Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Oddly, however, some classical coordination compounds of ruthenium with simple multidentate amines appear to be underrepresented in the literature; with tris(2-aminoethyl)amine (Tren), only one Ru(II)-Tren complex [9] and two Ru(III)-Tren [10] complexes having been reported previously (the former during our execution of this work). In this study, and Ru(DMSO) 4 Cl 2 as starting complexes, the first having recently been demonstrated to be a useful synthesis intermediate [11,12] .…”
Section: Introductionmentioning
confidence: 99%